Reply to Ellis et al.: Human niche construction and evolutionary theory - Larson, G; Erlandson, J; Zeder, M; Boivin, N; Crowther, A; Denham, T; Fuller, D; Petraglia, M (National Academy of Sciences, 2016)
We are pleased Ellis et al. found value in our recent synthesis of the deep history of human impacts on global ecosystems and agree that our paper should influence the current debate on if and how an Anthropocene epoch is defined. We also agree that the ecological consequences of human niche construction have profound and growing effects on the evolutionary trajectories of humans and other species living within human-altered ecosystems. Niche construction theory (NCT) provides an explicit framework for linking evolutionary and ecological processes into a coherent theory of biological evolution. Of special appeal to us as archaeologists is that NCT bridges biological and cultural evolution by including human culture and social learning within the mechanisms of evolutionary change, allowing scientists to address issues at the interface of human and natural systems. Some of us have contributed significantly to human NCT, addressing some of the very issues raised by Ellis et al. Finally, we agree that human transformations of ecosystems are inherently social processes—clearly humans are intensely social organisms—and that such processes result from long-term melding of biological and cultural evolution.